2012
DOI: 10.1074/jbc.m111.337642
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-214 Suppresses Growth and Invasiveness of Cervical Cancer Cells by Targeting UDP-N-acetyl-α-d-galactosamine:Polypeptide N-Acetylgalactosaminyltransferase 7

Abstract: Background: Recent research has uncovered tumor-suppressive and oncogenic potential of miRNAs. Results: miR-214 suppresses the proliferation, migration, and invasiveness of cervical cancer cells by targeting GALNT7. Conclusion: Down-regulation of miR-214 results in overexpressed GALNT7, contributing to tumorigenesis of cervical cancer. Significance: The identification of tumor suppressor miR-214 and its oncogenic target GALNT7 in cervical cancer cells is potentially valuable for cancer diagnosis and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
126
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(131 citation statements)
references
References 43 publications
4
126
1
Order By: Relevance
“…It was recently determined that microRNAs may play a role in the cellular response to radiotherapy [10,11]. miR-214 is an important miRNA that has been investigated in various tumor types and aberrantly expressed in various cancers and involved in the progress of malignant tumors [12][13][14][15][16]. miR-214 has been previously shown to promote the chemoresistance of human ovarian cancer [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently determined that microRNAs may play a role in the cellular response to radiotherapy [10,11]. miR-214 is an important miRNA that has been investigated in various tumor types and aberrantly expressed in various cancers and involved in the progress of malignant tumors [12][13][14][15][16]. miR-214 has been previously shown to promote the chemoresistance of human ovarian cancer [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports from other labs and our lab have shown that many miRNAs are aberrantly expressed in cervical cancer and that miRNAs can act as tumor suppressors (e.g., miR-302-367, miR-424, miR-214) [9][10][11][12] or enhancers (e.g., miR-205, miR-21, miR-19a/b) [13][14][15]. Although some progress has been achieved in the past decades, much more effort is needed to elucidate the occurrence and mechanism of cervical cancer.…”
Section: Introductionmentioning
confidence: 65%
“…Initiation of O-glycosylation is carried out by a family of GALNT sialyltransferase enzymes, including GALNT7, which catalyse the transfer of GalNAc to serine/threonine residues on target proteins to produce the Tn antigen (GalNAc-O-Ser/Thr) (Ten Hagen et al 2003). GALNT7 has been identified as oncogene in several types of cancer (Gaziel-Sovran et al 2011, Peng et al 2012, Li et al 2014b, …”
Section: Androgens Control O-glycan Biosynthesismentioning
confidence: 99%
“…Initiation of O-glycosylation Identified as oncogene in several types of cancer and controlled by micro-RNAs (Gaziel-Sovran et al , Peng et al 2012, Li et al 2014b, Nie et al 2015, Lu et al 2016 Upregulated in malignant PCa as part of a glycosylation gene signature (Barfeld et al 2014a). Androgen regulated and linked to prostate cancer cell viability ) GCNT1…”
Section: :3mentioning
confidence: 99%